KNOWLEDGE AND PERCEPTIONS OF VITAMIN D DEFICIENCY AMONG THE UNITED ARAB EMIRATES POPULATION - OSAMA MOHAMED IBRAHIM; NOOR KIFAH AL-TAMEEMI; DALIA DAWOUD (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objectives: The purpose of this study is to assess the Vitamin D deficiency awareness and perceptions between the United Arab Emirates (UAE) population. Methods: A cross-sectional study was done among the population of two emirates at the UAE: Abu Dhabi and Sharjah. Results: Overall, 434 participants completed the survey. Majority of people were aware of phenomenon of Vitamin D deficiency, but only 21.4% of them knew that sunlight is considered the main source of Vitamin D. Moreover, less than half of participants check their Vitamin D blood level regularly and around 55% of them follow-up with their physicians after completing the treatment. High proportion of participant females spend <1 h outdoors (60%) and use sunscreen daily (55%) that cause higher prevalence of Vitamin D deficiency among females than males (83% vs. 42%). Conclusion: This research gives some insights regarding the UAE population’s awareness and perceptions of Vitamin D insufficiency. Decreased awareness of sunlight exposure as a major source of Vitamin D, in addition to lifestyle, contributed to Vitamin D deficiency problem among the UAE population, in general, and in females, in particular.